Incorporating soil aggregate-associated indicators into evaluating ecological responses of degraded estuarine wetlands to freshwater replenishment at different intensity: A case study from the Yellow River Delta, China - Ziwen Ma (Elsevier, 2021)
Management intensity was considered an important factor in evaluating and regulating the anthropogenic restoration measures for a degraded ecosystem. By comparing selected conventional soil physicochemical, microbial and incorporating aggregate-associated indices between wetland plot with high-intensity freshwater replenishment (HI wetlands) and wetland plot with low-intensity freshwater replenishment (LI wetlands), edaphic responses of degraded estuarine wetlands to freshwater replenishment at different intensity were assessed in the present study. The results showed that high-intensity freshwater replenishment exerted better soil salinization and alkalization alleviation effects on degraded estuarine wetlands, which caused lower EC and pH values in HI wetlands than those in LI wetlands. And soil microbial biomass was promoted, with freshwater replenishment intensity increased, as indicated by MBC and total PLFAs. Minor alternation of soil microbial community composition was observed with an elevated abundance of arbuscular mycorrhizal fungi (AMF) in HI wetlands. On the other hand, freshwater replenishment at low intensity was found to contribute to organic matter accumulation, as indicated by both higher SOC concentrations and carbon stocks in LI wetlands than those in HI wetlands. And soil aggregate-associated indicators provided more scientific clues that freshwater replenishment at low intensity favored the formation of large macroaggregates, and thus supported higher soil aggregate stability. Moreover, a transfer of allocations of aggregate-associated carbon and nitrogen stocks from microaggregates to large macroaggregates was induced as the freshwater replenishment intensity decreased, and the principle governing factors were the proportion of large macroaggregates in soils, soil salinity and microbial decomposition rates based on multivariate statistical analysis. The findings of this study could provide basic data regarding soil physicochemical properties, microbial characteristics and soil structure stability in restored wetlands of the Yellow River Delta with freshwater replenishment at different intensity and guiding adaptive management strategies of freshwater replenishment to enhance the ecological functions of estuarine wetlands.